ジャカルタ国立大学の日本語学科における 2014-2015 の学年の大学 生に対して日本語の謝罪の発話行為の使用分析 - Purwanti; Hadinata, Febryan (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2016)
If someone says "sorry" that means the person is doing "speech act of apologize". Speechact of apologize are needed in everyday life in order to facilitate communication andharmony in life. Apologizing in Japanese are divided into some part, we called as strategycommunication. They are the beginning of conversation, explaining the reason, apologizingand closing of conversation. We need use the strategy communication when apologizing toavoid the mistake and misunderstanding between speaker and partner. I hope that peoplewho are studying Japanese can use strategy of speech act of apologize in Japanese properly.